2006
DOI: 10.1200/jco.2006.24.18_suppl.18600
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lymphangitis and cancer: Prospective series of 37 patients in palliative care

Abstract: 18600 Background: Lymphangitis of the lungs is an uncommon type of metastasis, mainly in breast, lung and gastric cancers, and has major impact in quality of life and an unfavorable prognosis. Survival is very poor: 50% in 3 and 15% in 6 months. Our objective was to evaluate prospectively quality of life in cancer patients with pulmonary lymphangitis, under palliative care. Methods: Patients with pulmonary lymphangitis, diagnosed either by lung biopsy (major criteria) or 3 minor criteria (cyto or histotologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…11 Low-dose corticosteroids decrease mortality risk and improve respiratory conditions. 10 However, this does not lead to significant radiological improvement, as seen in this patient. A systematic review and meta-analysis of case reports on PLC from 1970 to 2018 showed that glucocorticoids, in addition to other supportive treatments (such as oxygen and morphine), helped relieve the respiratory symptoms without affecting the imaging findings of PLC.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…11 Low-dose corticosteroids decrease mortality risk and improve respiratory conditions. 10 However, this does not lead to significant radiological improvement, as seen in this patient. A systematic review and meta-analysis of case reports on PLC from 1970 to 2018 showed that glucocorticoids, in addition to other supportive treatments (such as oxygen and morphine), helped relieve the respiratory symptoms without affecting the imaging findings of PLC.…”
Section: Discussionmentioning
confidence: 50%
“…9 Corticosteroids have been used to treat hypoxia in patients with PLC; however, the evidence to support this is limited. 10 Corticosteroids have been used to manage hypoxia in patients with PLC, although evidence to support their use is limited. In contrast, low doses of corticosteroids have been found effective in managing severe COVID-19 pneumonia, and dexamethasone has been reported to decrease mortality in ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…We agree that the issue of lymphangitis identified by Raj and colleagues is inadequately covered by the "optional descriptors" for lymphatic invasion presently offered in the 6th Edition of either the International Union Against Cancer (UICC) TNM Classification of Malignant Tumors 3 or the American Joint Committee on Cancer (AJCC) Manual of Cancer Staging. 4 We hope to study this in more detail in the prospective data base.…”
Section: In Replymentioning
confidence: 79%
“…First, relating to T descriptor, Lymphangitis carcinomatosis (LC), although uncommon, is a distressing form of metastatic lung cancer and has major impact in quality of life with an unfavorable prognosis. 3 LC can occur from lymphatic invasion from the primary tumor or nodal spread. 4 In other tumors, particularly, spread is thought to be hematogenous.…”
Section: To the Editormentioning
confidence: 99%